Management Accountant's Role and Functions in the Enterprise Resource Planning Environment - Author's Own Research into Enterprises in Poland; Rola i funkcje specjalisty do spraw rachunkowosći zarzadczej w warunkach zintegrowanych systemoẃ informatycznych- badania własne przedsiebiorstw w Polsce - Ewelina Zarzycka (Comparative Economic Research. Central and Eastern Europe, 2012)
ERP systems have revolutionized practically all aspects of business processes in enterprises. They help improve the processes by ensuring their integration. Ensuring integration between financial and non-financial data, an ERP package gives new quality to the management of enterprise value. All these features make ERPs particularly important for specialists responsible for providing management information and measuring performance of the company. This article seeks to answer whether the implementation of an ERP system has an effect on the management accountant's tasks and functions, especially in the field of performance measurement and internal reporting. The ERP impacts on the controller's role in the organization will be evaluated using field studies on six enterprises owned by multinational corporations. The question that should be asked here is whether controller's functions and tasks will also be unaffected. – – Zintegrowane systemy informatyczne rewolucjonizuja praktycznie wszystkie obszary działalnosći przedsiebiorstwa. Przyczyniaja sie one do ulepszenia procesoẃ biznesowych poprzez integracje wszystkich obszaroẃ działalnosći przedsiebiorstwa. Co wiecej dzieki tej technologii nastepuje zintegrowanie danych finansowych i niefinansowych przedsiebiorstwa, pozwalajac na jeszcze lepsze zarzadzanie wartosćia przedsiebiorstwa. Totezṡystemy ERP szczegoĺne znaczenie odgrywaja dla specjalistoẃ zajmujacych sie dostarczaniem informacji niezbednych dla zarzadzania przedsiebiorstwem. Celem badania jest prob́a odpowiedzi na pytanie czy zastosowanie zintegrowanego systemu informatycznego w przedsiebiorstwie zmienia zadania i funkcje specjalisty do spraw rachunkowosći zarzadczej. Na podstawie studium przypadku szesćiu przedsiebiorstw bedacych czesćia koncernoẃ miedzynarodowych zostaje dokonana ocena wpływu zastosowania ERP na role kontrolera w organizacji. Autor odpowiada roẃniezṅa pytanie czy w funkcjach i zadaniach kontrolera nie zaobserwowane zostana zmiany w zwiazku z implementacja ERP.
Keywords: 330